Morphological Changes Produced By Deltamethrin In Developing Mice (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the morphological changes produced by deltamethrin in developing mice. Design: Morphological study of in-utero deltamethrin treated mice. Setting: Animal house, Department of Zoology, University of the Punjab. Materials: 30 pregnant female mice of Swiss Webster variety of Mus musculus were chosen for the experiment and divided into control (C, 05 animals) and deltamethrin treated (DM, 25 animals) groups. The animals in DM group were divided into DM-I, DM-II, DM-III, DM-IV, and DM-V subgroups each consisting of 05. Each experimental subgroup animals were given 1.25, 2.50, 5.00, 10.00 and 15.00 µg of deltamethrin per g body weight orally (pumped into the gullet) on day 6, 8, and 10; and the control group animals were given 0.1 ml of corn oil (the vehicle used). The fetuses were recovered and examined on day 18 of gestation. Results: In-utero deltamethrin treated fetuses morphology revealed some abnormalities including distorted axis, sacral teratoma, microcephaly, anencephaly, micromelia, dysplasia of limbs, club foot, microgonathia and short tail. Conclusion: Deltamethrin is potentially harmful to the developing fetuses of mice, and may be equally harmful for the developing human too.